2008
DOI: 10.1002/anie.200704893
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Stereostructure of (+)‐Cytostatin by Fluorous Mixture Synthesis of Four Candidate Stereoisomers

Abstract: Dedicated to Professor Yoshito Kishi on the occasion of his 70th birthdayCytostatin (1) is a potent and selective inhibitor of protein phosphatase 2A that was isolated from the cultured broth of Streptomyces sp. by Ishizuka and co-workers (Scheme 1).[1] It inhibits lung metastasis of melanoma cells in mice and displays potent cytotoxic activity toward leukemia cell lines (inhibitory concentration; IC 50 = 42-65 nm). Ishizuka and coworkers assigned the two-dimensional structure (constitution) of cytostatin (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…2 Recent work has had a dual focus of introducing more efficient tagging strategies and solving structure problems by characterizing the natural product stereoisomer library members. 3 For example, we introduced a new double-tagging method to make macrosphelide stereoisomers that allows more compounds to be tagged with fewer fluorine atoms compared to prior tagging schemes. 4 And by characterizing the library members, we confirmed the structures of macrosphelides E and M and corrected the structure of macrosphelide D.…”
Section: Introductionmentioning
confidence: 99%
“…2 Recent work has had a dual focus of introducing more efficient tagging strategies and solving structure problems by characterizing the natural product stereoisomer library members. 3 For example, we introduced a new double-tagging method to make macrosphelide stereoisomers that allows more compounds to be tagged with fewer fluorine atoms compared to prior tagging schemes. 4 And by characterizing the library members, we confirmed the structures of macrosphelides E and M and corrected the structure of macrosphelide D.…”
Section: Introductionmentioning
confidence: 99%
“…Following the first total synthesis of fostriecin (Boger et al, 2001), at least nine total or formal syntheses have been reported (Chavez and Jacobsen, 2001;Esumi et al, 2002;Reddy and Falck, 2002;Miyashita et al, 2003;Maki et al, 2005;Trost et al, 2005). The total synthesis of cytostatin (Bialy and Waldmann, 2004;Lawhorn et al, 2006;Jung et al, 2008) and cytostatin analogs (Lawhorn et al, 2006;Jung et al, 2008) have also been reported. These studies have sparked renewed interest in the potential for development of more stable derivatives that may have utility as novel antitumor drugs.…”
mentioning
confidence: 99%
“…77,78 The oxidation of a complex substrate bearing a primary alcohol has been described by Hirama and co-workers (Scheme 5). ROMPM, 114,115,118,183 ROBn, 80,90,104,106,110,124,191,192 ROTr, 180 ROMe, 94,101,107,113,192 RONPhth, 88 RON=CMe 2 , 88 ArOAllyl, 193 ArOMe, 108,130,131,192,194,195 ArOBn, 127,131 ArOTBS, 174 R 2 NBoc, 174,[194][195][196][197] 208 This IBX analogue generates only water during the oxidation, while DMP releases acetic acid. When DMP was applied the required keto ester was obtained in only 60%, with 40% of the starting lactone recovered (Scheme 6).…”
Section: 76mentioning
confidence: 99%